The Future Classroom: Analyzing the Integration and Impact of Digital Technologies in Science Education (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
The present study is a systematic and bibliometric literature review aimed at evaluating the incorporation of digital technologies in science education and their subsequent impacts. The review exclusively utilizes the Scopus database and covers literature from January 2019 to December 2023. The primary focus is on empirical studies that investigate the use of digital technologies in science education and their effects on educational outcomes such as student engagement, motivation, and academic performance. Notably, the key findings reveal a significant increase in the number of publications during this period, indicating a growing interest in the role of digital technologies in enhancing science education. The review corroborates the transformation of science education through digital technologies such as augmented reality (AR), virtual reality (VR), and blended learning environments, which have made learning more interactive, personalized, and accessible. However, challenges such as the digital divide, resistance from educators, and the need for continuous professional development persist. These challenges emphasize the importance of strategies to enhance digital literacy among educators and promote equitable access to technology. The review recommends the development of comprehensive training programs for educators, ensuring that all students have access to the necessary digital tools, and maintaining robust data protection measures. By addressing these issues, the integration of digital technologies in science education can be optimized, resulting in enhanced educational outcomes and better preparation of students for a technology-driven world.